Efficacy, Safety and Tolerability of High dose Valsartan Hydrochloride in Essential Hypertension (Cardiovascular Journal, 2013)
Background: Studies across the world have demonstrated the efficacy of valsartan in lowering blood pressure in a variety of patient populations, several of them investigated higher doses of the drug. This study focuses on revealing safety and efficacy of valsartan at higher doses in Bangladeshi population. Current study is planned to evaluate the efficacy, safety and tolerability of daily dose of Valsartan 160 or 320 mg in the treatment of essential hypertension. Method: This is a multi-center, open-label, observational, non-comparative, clinical decision based titration, involving about 31 centers in Bangladesh. A total of 334 newly diagnosed adult patients with essential hypertension received valsartan at a dose of 160 mg or 320 mg as deemed necessary by physician were included to allow for an assessment of efficacy, safety and tolerability. The total duration of treatment with valsartan was 16 weeks. Primary parameter for efficacy was percentage responders to valsartan at 16 weeks, reduction in Mean sitting systolic blood pressure (MSSBP) and Mean sitting Diastolic blood pressure MSDBP, control rate (% patients) achieving SBP